Access to citizenship and the economic assimilation of immigrants - Gathmann, Christina; Keller, Nicolas (The economic journal, 2017)
Immigrants often have lower employment rates and earnings than natives. Does a more liberal citizenship policy improve their economic assimilation? Our empirical analysis relies on two reforms generating exogenous variation in the waiting time for citizenship. We find that faster access to citizenship improves the economic situation of immigrant women, especially their labour market attachment with higher employment rates, longer working hours and more stable jobs. Immigrants also invest more in host country-specific skills like language and vocational training. Faster access to citizenship seems a powerful policy instrument to boost economic integration in countries with traditionally restrictive citizenship policies. This article is protected by copyright. All rights reserved.